Understanding the Early Presentation of Mucopolysaccharidoses Disorders: Results of a Systematic Literature Review and Physician Survey. (21st December 2018) - Clarke, Lorne; Ellaway, Carolyn; Foster, Helen E.; Giugliani, Roberto; Goizet, Cyril; Goring, Sarah; Hawley, Sara; Jurecki, Elaina; Khan, Zaeem; Lampe, Christina; Martin, Ken; McMullen, Suzanne; et al.
As therapies are developed for rare disorders, challenges of early diagnosis become particularly relevant. This article focuses on clinical recognition of mucopolysaccharidoses (MPS), a group of rare genetic diseases related to abnormalities in lysosomal function. As quality of outcomes with current therapies is impacted by timing of intervention, minimizing time to diagnosis is critical. The objective of this study was to characterize how, when, and to whom patients with MPS first present and develop tools to stimulate earlier recognition of MPS. A tripartite approach was used, including a systematic literature review yielding 194 studies, an online physician survey completed by 209 physicians who described 859 MPS cases, and a global panel of MPS experts who distilled the findings. Red flag signs/symptoms were identified for cardiology, pediatric neurology, otorhinolaryngology, rheumatology, orthopedics, pediatrics, and general medicine and converted into simple, specialty-specific tools intended to facilitate early diagnosis of MPS, enabling improved patient outcomes.